Edge profile of commercially available square‐edged intraocular lenses: Part 2. Issue 6 (June 2019) - Nanavaty, Mayank A.; Zukaite, Ieva; Salvage, Jonathan
Abstract : Purpose : To analyze the sharpness of the posterior optic edge and edge thickness of intraocular lenses (IOLs) marketed with a square‐edged profile. Setting : University of Brighton and Brighton and Sussex University Hospitals NHS Trust, Brighton, England. Design : Laboratory study. Methods : Fourteen square‐edged 20.0 diopter IOLs were analyzed, including 9 hydrophobic IOLs (AF‐1, AF‐1 iSert, Clareon, EyeCee One Crystal, CT Lucia, Envista, EyeCee One, Vivinex iSert, and RayOne Hydrophobic) and 5 hydrophilic IOLs (Asphira, CT Asphina, Incise, Synthesis, and RayOne Hydrophilic). All the IOLs were scanned following a previously published standardized technique using environmental scanning electron microscopy. The posterior optic edges were scanned at a magnification of ×500 and ×200 to measure the radius of curvature of the posterior optic edges and the optic edge thickness. Results : The radius of curvature of the posterior optic edges ranged from 4.6 to 20.6 μm. Except for the Incise IOL (7.7 μm), all hydrophilic IOLs (Synthesis [10.6 μm], Asphira [13.7 μm], RayOne Hydrophilic [14.0 μm], CT Asphina [13.7 μm]) had a radius of curvature greater than 10.0 μm. For the hydrophobic IOLs, the radius of curvature was less than 10.0 μm for the Clareon (7.9 μm), EyeCee One Crystal (4.7 μm), Vivinex iSert (7.6 μm), and CT Lucia (4.6 μm), and greater than 10.0 μm for the Envista (19.7 μm), EyeCee One (13.7 μm), AF‐1 iSert (19.7 μm), AF‐1 (19.7 μm) and the RayOne Hydrophobic (20.6 μm). The Vivinex iSert (150.5 μm) and the Incise (218.2 μm) were the thinnest IOLs, and the RayOne Hydrophobic (375.8 μm) and RayOne Hydrophilic IOLs (477.1 μm) were the thickest of the hydrophobic and hydrophilic IOLs, respectively. Conclusions : Commercially marketed square‐edged IOLs still differed in the sharpness of the posterior optic edge. More hydrophobic IOLs have rounder edges than those studied 10 years ago. Variations in the edge profile of hydrophobic IOLs were greater compared with the hydrophilic IOLs.